2020
DOI: 10.15544/rd.2019.067
|View full text |Cite
|
Sign up to set email alerts
|

Innovative and Cross-Sectoral Clusters as Facilitators of Value Added Chains in Agriculture - Smart Agro Clusters in Romania

Abstract: Clusters play an important role in driving competitiveness, innovation and jobs creation in the EU. Romania currently has successful clusters in various economic sectors and services, including 7 clusters in agro-food. Agriculture has been and remains the support of the human existence, which is an important pillar of the Romanian rural economy.The agro-food sector had oscillating evolutions in the post-accession period, mainly generated by the need to get in line with the EU requirements. Stimulating smart te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Furthermore, the system approach identifies the main methodological principles that need to be implemented when designing a sustainable rural development strategy, such as the mandatory implementation of the plan. The central core of the strategic plan of agricultural enterprises should be considered the production program, which sets the The theoretical and methodological basis of this study consists of foreign and domestic fundamental works on the phenomenon of sustainable development, the use of cluster and foresight technologies, scenarios, and models to develop projects, forecasts, and roadmaps for strategic development of rural territorial entities [35][36][37].…”
Section: Methodological Study Designmentioning
confidence: 99%
“…Furthermore, the system approach identifies the main methodological principles that need to be implemented when designing a sustainable rural development strategy, such as the mandatory implementation of the plan. The central core of the strategic plan of agricultural enterprises should be considered the production program, which sets the The theoretical and methodological basis of this study consists of foreign and domestic fundamental works on the phenomenon of sustainable development, the use of cluster and foresight technologies, scenarios, and models to develop projects, forecasts, and roadmaps for strategic development of rural territorial entities [35][36][37].…”
Section: Methodological Study Designmentioning
confidence: 99%
“…Subsequently, Muraru-Ionel et al (2019) reported in their research that clusters play an important role in promoting competitiveness, innovation and job creation in the EU. The Agri-Food sector in Romania had fluctuating developments in the post-accession period, mainly due to the need to comply and align with EU requirements.…”
Section: Clusters In the Field Of Agri-food Products (Dairy Agri-food...mentioning
confidence: 99%
“…The analysis and study of all results and conclusions of previous research and studies leads us to some observations. Firstly, From the study of Abrhám (2014), the research by Muraru-Ionel et al (2019) and the research of Bashynska et al (2022), it is shown that although to date a single concept for the creation of clustering mechanisms has not been developed, nevertheless each country has identified its own set of successful practices for the implementation of policy elements for cooperative formations taking into account national characteristics for the approach of cooperative formations (clusters). Thus, the clusters have evolved into a key tool for the formulation and implementation of the economic development policy of the regions and the economy as a whole in several countries, and this, because they have become one of the main driving forces and determining factors of the competitiveness and efficiency which has been confirmed by world experience.…”
Section: Clusters In the Field Of Agri-food Products (Dairy Agri-food...mentioning
confidence: 99%
See 1 more Smart Citation
“…Питання сутності кластерів в економіці та їх важливості для забезпечення сталого розвитку були предметом багатьох теоретичних та емпіричних досліджень [5]. Європейський досвід свідчить, що у регіональних стратегіях розумної спеціалізації кластери допомагають забезпечити ефективне управління ланцюгами доданої вартості в агропродовольчому секторі [6].…”
Section: рис 1 графічна модель функціонування кластера як відкритої с...unclassified